Estrategias argumentativas utilizadas por los estudiantes de la institución educativa Divino Niño de Tierra Grata (Chinú) en el análisis de hechos históricos culturales (2019)
In the teaching of science, the development of argumentation should be privileged, in favor of the construction and understanding of knowledge in the classroom. The present study is a contribution to their development and to the didactics of science teaching through the analysis of classroom discourse in secondary school students. In this, we reflect on the incidence of argumentative strategies and the quality of the arguments in the conceptual evolution of historical cultural events (Identity, History and Culture), assessing the quality model of the arguments of Sampson and Clark (2009) and their relationship with the argumentative model of Candela (2006) analyzing its implications in the definition of contents that oscillate between common knowledge and scientific knowledge.